Design and development of i-Dietkids courseware for hearing impaired children guided by courseware engineering methodology / Norizan Mohamad … [et al.] - Mohamad, Norizan; Mohamed@Omar, Hasiah; Syed Yasin, Sharifah Nurulhikmah; Muhammud, Adida; Mohd Abd Majid, Hayati Adilin (Faculty of Computer and Mathematical Sciences, 2021)
Designing and developing a multimedia courseware requires a structured approach and many novices are not aware of this. This paper discusses on the design and development of i-DietKids courseware which is guided by the Courseware Engineering Methodology (CEM). CEM is a modelbased approach that has been applied mainly to aid those who are new to courseware design and development. The CEM process consists of four models; first, the pedagogical model that is related to the pedagogical features of the courseware. Second, the conceptual model that deals with the software engineering features of the design; third, the interface model that relates to the interface of the courseware, and finally the hypermedia model that deals with the navigational concerns of the courseware. Every model deal with the various aspects of the development process. Usability testing was conducted on the iDietKids courseware, and the result has shown a very promising and feasible consumption in the educational setting. It is hoped that this i-DietKids courseware will be used to continuously educate hearing impaired children on the importance of nutritious food intake.